ANALISIS KEMAMPUAN INKUIRI SISWA DI SEKOLAH DASAR - Ayurachmawati, Puji; Widodo, Ari (Universitas Pendidikan Indonesia, 2016)
Abstract: Abstract: This study aims to describe the ability of inquiry held by elementary school students at the time given inquiry-based activities. The method used is a qualitative descriptive conducted in one of the elementary schools in the city of Palembang, South Sumatra. The data collection is done by providing inquiry-based student activity sheet containing seven stages of activity. Sheets inquiry activities done by the students of Class I to Class IV Elementary School. Total student working inquiry activity sheet totaled 178 people. The results showed that there are five faculties of inquiry that arise and have a difference in every level of ability from Class I - Class VI. Fifth ability of inquiry that emerged is experiencing growth of the number of students who mastered at each level and the composition of each capability. Classically students at the level of Class I and Class II is not yet mastered the ability of inquiry.Keywords: the ability of an inquiry, the elementary school studentsAbstrak: Penelitian ini bertujuan untuk mengetahui gambaran kemampuan inkuiri yang dikuasai siswa Sekolah Dasar pada saat diberikan kegiatan berbasis inkuiri. Metode penelitian yang digunakan adalah deskriptif kualitatif yang dilaksanakan di salah satu Sekolah Dasar di kota Palembang, Sumatera Selatan. Pengumpulan data dilakukan dengan memberikan siswa lembar kegiatan berbasis inkuiri yang berisi tujuh tahapan kegiatan. Lembar kegiatan inkuiri dikerjakan oleh siswa Kelas I hingga Kelas IV Sekolah Dasar. Total keseluruhan siswa yang mengerjakan lembar kegiatan inkuiri berjumlah 178 orang. Hasil penelitian menunjukkan bahwa terdapat lima kemampuan inkuiri yang muncul dan memiliki perbedaan pada setiap kemampuan dari tingkatan Kelas I – Kelas VI. Kelima kemampuan inkuiri yang muncul ini mengalami perkembangan dari jumlah siswa yang menguasai pada setiap jenjang dan komposisi pada setiap kemampuan. Secara klasikal siswa pada tingkatan Kelas I dan Kelas II dikatakan belum menguasai kemampuan inkuiri.Kata kunci : kemampuan inkuiri, siswa sekolah dasar